The Role of Student Engagement in Mediating the Influence of Internships and Entrepreneurship Development Programs on Entrepreneurial Intention: A Case Study at SMKN 1 Ngawi - Muthoharoh, Jamilatul; Pratiwi, Dian (Dinasti Publisher, 2026)
This study investigates the effect of internship programs and entrepreneurship development on students' entrepreneurial interest, mediated by student engagement. The research involved 74 students of the Digital Business Department at SMKN 1 Ngawi, selected from a population of 90. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the results indicate that both internships and entrepreneurship development have a positive but insignificant effect on entrepreneurial interest, while they significantly enhance student engagement. Moreover, students engagement positively and significantly influences entrepreneurial interest, mediating the indirect effect of internships and entrepreneurship development. These findings suggest that fostering student engagement is crucial for strengthening entrepreneurial interest, emphasizing the need for quality internships and entrepreneurship programs that actively involve students in learning.